EP487 Panoramic view of endometrioid endometrial cancer in turkey: a retrospective, multicenter study of turkish society of gynecologic oncology (TRSGO-END002). (1st November 2019) - Çelik, E; Gülseren, V; Özge Kayan, B; Öz, M; Kocaman, E; Akgöl, S; Alemdoroğlu, S; Topuz, S; Güngördük, K; Demirkiran, F; Meydanli, MM; Akbayir, Ö; et al.
Abstract : Introduction/Background: The purpose of this study was to investigate prognostic factors associated with overall survival (OS) in endometrioid endometrial cancer (EC). Methodology: A multicenter, retrospective department database review was performed to identify patients with endometrioid EC at seven high-volume gynecologic oncology centers in Turkey. A total of 4993 women who had undergone primary surgery between 1999 and 2018 were included. Women were staged according to the 2009 FIGO staging system. Kaplan-Meier method was used to generate survival data. Factors predictive of outcome were analyzed using Cox proportional hazards models. Results: Three thousand two hundred and nineteen women (64.5%) were classified as stage IA, 1034 (20.7%) as IB, 286 (5.7%) as II, 72 (1.4%) as IIIA, 15 (0.3%) as IIIB, 173 (3.55) as IIIC1, 128 (2.6%) as IIIC2, and 66 (1.3%) as stage IV. The median age at surgery was 58 years (range, 21–94 years), and the median duration of follow-up was 47 months (range, 3–227 months). For the entire cohort, the 5-year disease-free survival was 75.1% whereas the 5-year OS was 82.2%. Age ≥60 years (Hazard ratio [HR]: 1.21, 95% confidence interval [CI]:1.06–1.40; p=0.005), myometrial invasion (MMI) ≥1/2 (HR: 1.19, 95% CI:1.02–1.41; p=0.02), lymphovascular space invasion (LVSI) (HR: 1.29, 95% CI:1.05–1.58; p=0.01), and baseline serum CA 125 ≥35 U/ml (HR: 1.29, 95% CI:1.08-1.55; p=0.005) were identified as independent prognostic factors for decreased OS. Conclusion: Age ≥60 years, MMI ≥1/2, LVSI, and baseline serum CA 125≥35 U/ml seem to be independent prognostic factors for decreased OS in Turkish endometrioid EC population. Disclosure: Nothing to disclose.